Assessment of sexual assaults in pediatric settings at the Sourô Sanou University Hospital in Bobo-Dioulasso - Barro, Makoura; Naon, Sarah Evlhe; Yonaba, Caroline; Tinto, Sidanoma Maréta; Bonzi, Yèpan Flavie Pascaline; Nacro, Sahoura Fatimata; Kalmogo, Angèle; Sanogo, Bintou; Somé, Der Adolphe (Pediatric Review: International Journal of Pediatric Research, 2024)
Introduction: Sexual assault is a worldwide public health problem. It is one of the most appalling forms of child abuse. The aim is to take stock of sexual assaults in pediatric settings at the Souro Sanou University Hospital in Bobo-Dioulasso. Methods: This was a descriptive, prospective study covering the period from 2013 to 2021. All children victims of sexual abuse aged between 0 and 15 years were included. Descriptive statistics were used Results: we had a sample of 32 patients, 31 females. Mean age was 9.23 years. The children were most often abused during working hours (68.75%), outside the family environment (90.62%), by a single aggressor (78.125%) belonging to the victim’s entourage (68.75%). For most of our victims, this was the first episode (87.5%), and genital contact was the most frequent form of sexual contact, with vaginal penetration in (71.87%) of cases. In half the cases, the assailant had used physical force; in 18.75% of cases, a knife was used, and in 6.25% of cases, the assailant was under the influence of drugs. Less than half the victims had consulted within 72 hours, and the genital examination revealed vulvar ulcerations in 37.5% of cases, and hymenal damage in 28.12%. HIV serology was carried out in all patients, 75% had hepatitis B serology and 62.5% had syphilitic serology. Pregnancy tests were performed in 7 patients. None of these tests came back positive. Conclusion: Sexual assault of children, a very sensitive subject often hushed up, remains a reality in our country.